IL-4 Is a Key Requirement for IL-4- and IL-4/IL-13-Expressing CD4 Th2 Subsets in Lung and Skin - Prout, Melanie Sarah; Kyle, Ryan L.; Ronchese, Franca; Le Gros, Graham (Frontiers in Immunology, 2018)
Although IL-4 is long associated with CD4 Th2 immune responses, its role in Th2 subset development in non-lymphoid tissues is less clear. We sought to better define IL-4’s role in CD4 Th2 responses by using transgenic mice that express a dual IL-4 AmCyan/IL-13 DsRed (IL-4AC/IL-13DR) fluorescent reporter on an IL-4-sufficient or IL-4-deficient background. Using primary Th2 immune response models against house dust mite or Nippostrongylus brasiliensis (Nb) allergens, we examined the requirement for IL-4 by each of the defined Th2 subsets in the antigen draining lymph node, skin, and lung tissues. In the lymph node, a CXCR5+PD-1+ T follicular helper (Tfh) and a CXCR5loPD-1lo Th2 subset could be detected that expressed only IL-4AC but no IL-13DR. The number of IL-4AC+ Tfh cells was not affected by IL-4 deficiency whereas the number of IL-4AC+ Th2 cells was significantly reduced. In the non-lymphoid dermal or lung tissues of allergen primed or Nb-infected mice, three strikingly distinct T cell subsets could be detected that were IL-4AC, or IL-4AC/IL-13DR, or IL-13DR CD4. The IL-4- and IL-4/IL-13-expressing subsets were significantly reduced in IL-4-deficient mice, while the numbers of IL-13-expressing CD4 T cells were not affected by IL-4 deficiency indicating that other factors can play a role in directing the development of this Th2 subtype. Taken together, these data indicate that the appearance of IL-4-expressing Tfh cells in the lymph node is not dependent on IL-4 while the appearance of IL-4-expressing Th2 subsets in the lymph node and IL-4, IL-4/IL-13-expressing Th2 subsets in skin and lung tissues of antigen primed mice is significantly IL-4 dependent.